Essentials public health functions and public health genomics in Ecuador (Research, Society and Development, 2021)
Aim: This paper aims to analyze the EPHF in MG in Ecuador as a framework for integrating it into clinical practice. It also aims to contribute to the scientific and social debate on the MG role, considering it the most advanced science field today. Context: the Essentials Public Health Functions (EPHF) are actions for specific purposes necessary to achieve the central objective of Public Health (PH), which is to improve, promote, protect, and restore the population's health through collective action. Medical Genetics (MG) and Genomics are still in construction between public policies, especially in developing countries, and deserve an in-depth approach in this context. Discussion: We understand collective health as an inter-institutional and interdisciplinary social practice, which involves both the State and civil society, aims at protecting and improving people's health. It implies population or community interventions; it includes the responsibility to ensure access and health care quality. Within this practice are the EPHF, defined as actions carried out for specific purposes necessary to achieve the PH Practice's central objective. Each function's operation depends on a sufficient definition of contents, objectives, and activities and on the specific assignment of who is responsible for their execution. Conclusion: The EPHF guides public health policies in Latin America and Ecuador. From this perspective, medical genetics and genomics must be included as a priority in the country's public policy. In this review, we propose the activities to be implemented in this context. This challenge requires political and scientific leadership.